Oral health status of nursing staff in Ilembula, Wanging’ombe District, Njombe region, Tanzania: a cross-sectional study - Bensel, Tobias; Erhart, Imke; Megiroo, Simon; Kronenberg, Werner; Bömicke, Wolfgang; Hinz, Sebastian (BMC oral health, 2022)
Owing to the reduced dental treatment infrastructure in the Tanzanian highlands, maintaining good oral health is a challenge for not only the general population but also individual professional groups. In this study, the caries prevalence and, subsequently, the prosthetic treatment needs of the nurses of the Ilembula Lutheran Hospital (ILH) and Ilembula Institute of Health and Allied Sciences (IIHAS), Tanzania, were investigated.
Gesehen am 13.07.2022